Ocean Sensitivity to Periodic and Constant Volcanism - Dogar, Muhammad Mubashar (Sci Rep, 2020)
It is strongly believed that the explosive eruptions produce negative radiative forcing that causes long-term perturbations in the ocean. Moreover, it is anticipated that a sporadic strong cooling should initiate more vigorous vertical mixing of the upper ocean, and therefore cools the ocean more effectively than a uniform radiative forcing. However, the long-term simulations show that on average the ocean heat content responses to periodic and constant forcings are comparable. To better understand this controversy and to better quantify the post-eruption oceanic response, we conducted two sets of parallel simulations, the first with a uniform/constant volcanic forcing and the second one with a periodic volcanic forcing of magnitude 1×, 5×, 10× and 30× of Pinatubo size eruption using Geophysical Fluid Dynamics Laboratory’s coupled model, CM2.1. We systematically compared the effect of periodic volcanic forcing with an equivalent time-average volcanic cooling. Our results reveal that on average, volcanic-induced perturbations in Ocean Heat Content (OHC), and sea-level rise (SLR) following uniform and periodic eruptions are almost identical. It further emphasizes that the strength of ocean heat uptake at different ocean depths is mainly driven by the strength of the Atlantic Meridional Overturning Circulation (AMOC). These findings are important for ocean initialization in long-term climate studies, and geoengineering applications. It would help to unfold uncertainties related to ocean relaxation process, heat storage, and redistribution.